2023
DOI: 10.1038/s41598-023-39433-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diabetes care cascade and compliance with WHO global coverage targets in Iran based on STEPS survey 2021

Sina Azadnajafabad,
Naser Ahmadi,
Negar Rezaei
et al.

Abstract: This study aimed to investigate the diabetes mellitus (DM) and prediabetes epidemiology, care cascade, and compliance with global coverage targets. We recruited the results of the nationally representative Iran STEPS Survey 2021. Diabetes and prediabetes were two main outcomes. Diabetes awareness, treatment coverage, and glycemic control were calculated for all population with diabetes to investigate the care cascade. Four global coverage targets for diabetes developed by the World Health Organization were ado… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(61 reference statements)
1
2
0
Order By: Relevance
“…Consistent with our findings, Babaniamansour et al [ 31 ] also found that 49% of the 562 subjects diagnosed with T2DM exhibited inadequate glycemic control. Recently, based on STEPS survey in Iran, poor glycemic control has been reported in 51.4% of diabetic patients [ 23 ] that was roughly the same as our study. Alzaheb et al conducted a study on adult patients with T2DM in Saudi Arabia and reported a higher prevalence of poor glycemic control compared to the results of our study [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with our findings, Babaniamansour et al [ 31 ] also found that 49% of the 562 subjects diagnosed with T2DM exhibited inadequate glycemic control. Recently, based on STEPS survey in Iran, poor glycemic control has been reported in 51.4% of diabetic patients [ 23 ] that was roughly the same as our study. Alzaheb et al conducted a study on adult patients with T2DM in Saudi Arabia and reported a higher prevalence of poor glycemic control compared to the results of our study [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, studies on the association of multimorbidity and blood glucose control are very limited; while, the majority of studies examining the correlation between multimorbidity and glycemic control have primarily concentrated on hypoglycemia [ 20 , 21 ]. However, prior research suggests that uncontrolled diabetes, leading to hyperglycemia, remains the primary concern in developing countries [ 22 , 23 ]. Thus, despite the growing prevalence of diabetes and its complications, there is a dearth of data regarding factors associated with glycemic control [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Controls were T2DM patients with the same criteria as above who had an HbA1c measurement equal to or less than 8%, i.e. fairly controlled T2DM [ 15 , 16 ]. Patients were recruited from the Imam-Reza University Hospital, Tabriz University of Medical Sciences, Tabriz, Iran.…”
Section: Methodsmentioning
confidence: 99%